The Association Between Spicy Food Intake and Risk of Hyperuricemia Among Chinese Adults - Luo, Qinwen; Ding, Rui; Chen, Liling; Bu, Xiaoqing; Xiao, Meng; Liu, Xiang; Wu, Yunyun; Xu, Jingru; Tang, Wenge; Qiu, Jingfu; Ding, Xianbin; Tang, Xiaojun (Frontiers in Public Health, 2022)
Hyperuricemia is associated with substantial health and economic burden all over the world. Dietary habits are an important influencing factor of hyperuricemia. This study aimed to investigate the relationship between spicy food intake and hyperuricemia based on a large population. 22 125 individuals aged 30–79 were enrolled in China Multi-Ethnic Cohort (CMEC), Chongqing region. Spicy food intake information was collected by a standardized questionnaire. The association between spicy food intake and hyperuricemia was estimated by multivariable logistic regression models and multiple linear regression models. Additionally, we explored these relations in subgroups stratified by sex and age. Furthermore, sensitivity analyses were conducted to verify the stability of current findings. After controlling for potential confounders, compared with participants who never consumed spicy food and consumed less hot, participants who ate 3-5 days per week and very hot had the highest risk of hyperuricemia; the ORs(95%CIs) were 1.28(1.09,1.50) and 1.22(0.92,1.63), respectively. And the corresponding ORs(95%CIs) for each level increment in the frequency and degree of pungency in spicy food intake were 1.04(1.010,1.07) (P trend=0.009) and 1.15(1.04,1.26) (P trend=0.004). Further in sex-stratified and age-stratified analysis, similar positive associations were observed among males and those aged 30-59, but no significant association was found among females and those aged 60-79. In the linear regression models, 3-5 days per week and moderate pungency in spicy food intake were associated with 5.21µmol/L (95%CI:1.72,8.70) and 4.69µmol/L (95%CI: 1.93,7.45) higher serum urate level. Results in further subgroup analysis were generally consistent with the logistic regression models. This study suggests that spicy food intake may be a risk factor for hyperuricemia, especially in males and younger people, and more studies are warranted to verify the causal associations.